2016
DOI: 10.5144/0256-4947.2016.21.3.1130
|View full text |Cite
|
Sign up to set email alerts
|

Allotransplantation of macroencapsulated parathyroid cells as a treatment of severe postsurgical hypoparathyroidism: case report

Abstract: Persistent hypoparathyroidism, a condition associated with major inconvenience and potential morbidity, is more difficult to treat than other hypofunctional endocrine disorders. Therapeutic alternative in severe postsurgical hypoparathyroidism is allotransplantation of macroencapsulated parathyroid cells. With this technique, it is possible to implant cells or tissues of parathyroid origin to replace them in such patients without immunosuppression. At the present time, durable results have only been reported i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 6 publications
0
14
0
2
Order By: Relevance
“…The use of PTH and its derivatives has been tested with some success in the treatment of hypoparathyroidism, and the use of PTH (1-84) has been approved by American and European agencies (FDA and EMA) and will be discussed in Section 9 (124). Furthermore, perspectives point out to the use of allografts of macroencapsulated parathyroid cells, but studies in this regard are still in experimental phases (125).…”
Section: Treatment Of Chronic Hypocalcemiamentioning
confidence: 99%
“…The use of PTH and its derivatives has been tested with some success in the treatment of hypoparathyroidism, and the use of PTH (1-84) has been approved by American and European agencies (FDA and EMA) and will be discussed in Section 9 (124). Furthermore, perspectives point out to the use of allografts of macroencapsulated parathyroid cells, but studies in this regard are still in experimental phases (125).…”
Section: Treatment Of Chronic Hypocalcemiamentioning
confidence: 99%
“…Agha et al tried to autotransplant tissue pieces (about 1 to 2 mm; Agha et al, 2016) from hyperparathyroidism patients so that immunological rejection was not worried. Other attempts process the cells or tissue pieces so that they can work well in allogeneic conditions (Khryshchanovich & Ghoussein, 2016; Tibell et al, 2001; listed in Table 2 as pre‐TE‐PTG trials and the conceptual graph shown in Figure 3a).…”
Section: Parathyroid‐related Diseases and Clinical Therapiesmentioning
confidence: 99%
“…Overdosed PTH (1‐34) has the potential to bring hypocitraturia that is harmful to kidneys (Gafni et al, 2018). As for transplantation, allotransplantation was first used in postsurgical hypoparathyroidism but is still not popular enough considering the shortage of safe and functional cell or tissue resources (Agha et al, 2016; Khryshchanovich & Ghoussein, 2016; Tibell et al, 2001). Moreover, Jo et al summarized several attempts combined biomaterial scaffolds and rhPTH alone excepting cells for transplanting to cure hypoparathyroidism, and the lack of feedback regulation means it is not an ideal way for long‐term effect (Jo et al, 2019).…”
Section: Parathyroid‐related Diseases and Clinical Therapiesmentioning
confidence: 99%
“…However, hormone replacement therapy is the most expensive treatment option and long‐term effects of kidney functionality is not known yet . Besides, various techniques are defined for PA, such as cultured cell transplantation, tissue transplantation, and microencapsulated cell transplantation . Microencapsulation technique is more successful than other techniques because it avoids the immune system.…”
Section: Introductionmentioning
confidence: 99%